1999
DOI: 10.1161/01.atv.19.8.1975
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Lipase ( LIPC ) Promoter Polymorphism in Men With Coronary Artery Disease

Abstract: Abstract-Hepatic lipase is an important determinant of plasma HDL concentration and LDL subclass distribution and may therefore influence susceptibility to coronary artery disease (CAD). To assess the effect of genetic variation in hepatic lipase activity on CAD susceptibility, we determined the frequency of the Ϫ514T allele of hepatic lipase in white men with CAD and in controls who did not have CAD. In men with CAD, postheparin plasma hepatic lipase activity was 15% to 20% lower in heterozygotes and 30% lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 34 publications
(26 reference statements)
1
21
1
1
Order By: Relevance
“…In HL promoter analysis, more Ϫ514T heterozygotes, but fewer Ϫ514T homozygotes, were found in CAD patients, suggesting the complex nature of atherogenicity Cohen et al 1999). However, that finding was not confirmed in Finns or American whites (Tahvanainen et al 1998;Shohet et al 1999). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In HL promoter analysis, more Ϫ514T heterozygotes, but fewer Ϫ514T homozygotes, were found in CAD patients, suggesting the complex nature of atherogenicity Cohen et al 1999). However, that finding was not confirmed in Finns or American whites (Tahvanainen et al 1998;Shohet et al 1999). …”
Section: Discussionmentioning
confidence: 90%
“…Thus, HL promoter variation had significant effects on the variability of HDL-C levels, predominantly through the Ϫ514C/C genotype decreasing HDL-C levels in the Japanese population. HL promoter genotypes have been well characterized in Caucasian populations (Guerra et al 1997;Nie et al 1998;Grundy et al 1999;Murtomaki et al 1997;Jansen et al 1997;Tahvanainen et al 1998;Shohet et al 1999;Jansen et al 1999). However, there are a few reports on other populations Zambon et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Grundy et al reported an association of the -514T allele with increased plasma HDL-C concentrations in only healthy, normotriglyceridemic men who did not smoke or use lipid-lowering drugs . Also, Shohet et al showed that the -514T allele was associated with higher HDL-C levels only in healthy men, and not in men with CAD (Shohet et al, 1999). In the only other study on Koreans, the hepatic lipase C-514T polymorphism was not associated with HDL-C in either men or women, and was only associated with apoB levels in women with CAD, and with apoA1 levels in healthy men (Hong et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Intriguingly, reports of higher CAD risk and lower HDL concentrations among those with the Ϫ480C rather than the Ϫ480T allele also exist (115,116). The LIPC Ϫ480C/T polymorphism has been recently associated with insulin resistance (117,118).…”
Section: Hepatic Lipasementioning
confidence: 99%